Über die Geometrie des Normalsystems Partiellen Differentialgleichungen höherer Ordnung - Bliznikas, V. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. И. Близникас. О геометрии нормальных систем дифференциальных уравнений высшего порядка с частными производнымиV. Bliznikas. Aukštesnės eilės diferencialinių lygčių sistemų su dalinėmis išvestinėmis geometrijos klausimu